Evaluasi dan Uji Daya Hambat Sabun Kertas Ekstrak Daun Mangga (Mangifera Indica L) Terhadap Pseudomonas Aeruginosa dan Candida Albican - TWELVIYANI, Arni Twelviyani; Wattiheluw, Muhammad Hasan (INSTITUT AGAMA ISLAM NEGERI AMBON, 2025)
In this study, mango extract was formulated with varying concentrations of paper soap. Assessment of paper soap includes testing organoleptic type, pH value, foam height, and water content. The purpose of the study was to assess and test paper soap formulations containing mango leaf extract (Mangifera indica L.) in inhibiting the growth of Pseudomonas aeruginosa and Candida albicans. Mango leaves are known to have active connections that may be antiseptic. The inhibition test was performed by the pitting diffusion method. The diameter of the inhibition zone formed around the wells was measured after incubation using a ruler. The results showed that the formulation of mango leaf extract has excellent physical properties and does not cause irritation to the skin at certain concentrations and formulations. Inhibition tests show that soap from mango leaf extract is not effective for inhibiting the growth of Pseudomonas aeruginosa, but can inhibit the growth of Candida albicans with an increase in the inhibition zone as well as an increase in extract concentration with a weak category. Mango leaf extract paper soap cannot be an antiseptic soap on Pseudomonas aeruginosa but can be an antiseptic on Candida albicans. Keywords: Antiseptic, Candida albicans, Pseudomonas aeruginosa